Effects of Pig Dung and Poultry Manure With Plant Residues on the Production of Some Fruit Vegetables - Adigun, M. O.; Babalola, O.A. (International Multidisciplinary Research Journal, 2014)
The field experiment was carried out during the raining season at Organic Agricultural Farm of the Federal University of Agriculture, Abeokuta. Nigeria. Compost was prepared using pig dung and poultry manure with plant residue. It was applied at the rate of 0 and 10t ha-1 replicated three times. The observation on growth parameter showed that at 5 WAP okra with composted poultry manure was low although there was increase at 7 and 9 WAP. The observation on growth parameter showed that at 5 WAP okra with composted poultry manure was low than composted pig manure and no amendment but later showed increase in height at 7 and 9 WAP while pepper with poultry manure was higher than composted pig manure and no amendment which later increase in highest. Observation on yield parameter revealed that okra with composted pig manure had the highest number of fruits than pepper with composted pig manure. The soil micro biological parameters after adding compost showed that pepper with no amendment had the highest viable counts than pepper composted pig dung and poultry manure than okra with composted pig manure and no amendment. Fungal counts were high in un-amended soil planted with pepper than all other treatments. Microbial biomass carbon was high in soil amended with composted poultry manure planted with okra than all other treatment. Microbial biomass phosphorus was high in soil amended with poultry manure planted with okra than other treatments and microbial biomass nitrogen was high in soil amended with poultry manure planted with pepper and that of okra with pig manure. The soil microbiological parameters were affected by treatments.